1991
DOI: 10.1128/jb.173.17.5558-5563.1991
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Agrobacterium tumefaciens T-DNA transfer by overdrive depends on a flanking sequence but not on helical position with respect to the border repeat

Abstract: T-DNA transfer by Agrobacterium tumefaciens depends on the right border repeat of the T-DNA and is greatly stimulated by overdrive, an adjacent sequence. We report that the function of overdrive does not depend on helical position with respect to the border repeat. A synthetic 24-bp overdrive and a 12-bp region containing a fully conserved 8-bp core overdrive sequence stimulated virulence equally, but full function required additional bases to the left of the 24-bp sequence.Agrobacterium tumefaciens causes cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Although the overdrive element is believed to function in a position-independent manner with respect to the right border (Shurvinton and Ream, 1991), we found that a single basepair insertion between St02 and upstream DNA reduced transformation frequencies of pSIM579 about 2-fold (Fig. 3A).…”
Section: The Influence Of Flanking Dna On the Efficacy Of Right Bordementioning
confidence: 82%
See 1 more Smart Citation
“…Although the overdrive element is believed to function in a position-independent manner with respect to the right border (Shurvinton and Ream, 1991), we found that a single basepair insertion between St02 and upstream DNA reduced transformation frequencies of pSIM579 about 2-fold (Fig. 3A).…”
Section: The Influence Of Flanking Dna On the Efficacy Of Right Bordementioning
confidence: 82%
“…We found the enhancing activity of this region to require at least six pyrimidine residues at conserved positions. The sequence and spacing requirements of the ACR domain may explain why certain previously characterized Ti plasmid mutants displayed reduced virulence (Shurvinton and Ream, 1991). For instance, the impaired activity of mutant WR1803 is associated with an insufficient number of pyrimidine residues at conserved positions, and the low efficiency of WR1804 is linked to a lack of adeninerich spacers.…”
Section: Discussionmentioning
confidence: 99%
“…These plasmids were introduced into the virE2 null strain WR5000. For quantitative tumorigenesis assays, we infected potato tuber disks (7-mm diameter) as described previously (53). A. tumefaciens was grown overnight at 28ЊC with aeration in YEP broth containing the appropriate antibiotics, harvested by centrifugation, and suspended in phosphatebuffered saline (3 mM monobasic potassium phosphate, 10 mM dibasic sodium phosphate, 120 mM sodium chloride; pH 7.2) (45).…”
Section: Methodsmentioning
confidence: 99%
“…Overdrive sequences enhance the transmission of T-strands to plants, although the molecular mechanism of how this occurs remains unknown (131,156,256,291,336,337,345). Early reports suggested that the VirC1 protein binds to the overdrive sequence and may enhance T-DNA border cleavage by the VirD1/VirD2 endonuclease (322).…”
Section: Molecular Basis Of Agrobacterium-mediated Transformation Whamentioning
confidence: 99%